Mendelian randomisation study of the effects of known and putative risk factors on pancreatic cancer - Lu, Ye; Gentiluomo, Manuel; Lorenzo Bermejo, Justo; Morelli, Luca; Obazee, Ofure; Campa, Daniele; Canzian, Federico (Journal of medical genetics, 2020)
Background Observational studies have reported multiple risk factors for pancreatic ductal adenocarcinoma (PDAC). Some are well established, like tobacco smoking, alcohol drinking, obesity and type 2 diabetes, whereas some others are putative, such as allergy and dietary factors. Identifying causal risk factors can help establishing those that can be targeted to contribute to prevent PDAC. - Objective We sought to investigate the possible causal effects of established and putative factors on PDAC risk. - Methods We conducted a two-sample Mendelian randomisation (MR) study using publicly available data for genetic variants associated with the factors of interest, and summary genetic data from genome-wide association studies of the Pancreatic Cancer Cohort Consortium (PanScan) and the Pancreatic Cancer Case-Control Consortium (PanC4), including in total 8769 cases and 7055 controls. Causality was assessed using inverse-variance weighted, MR-Egger regression and weighted median methods, complemented with sensitivity and radial MR analyses. - Results We found evidence for a causal effect of body mass index (BMI) on PDAC risk (OR 1.43, 95% CI 1.20 to 1.71, p=8.43×10−5). Fasting insulin (OR 2.84, 95% CI 1.23 to 6.56, p=0.01), low-density lipoprotein cholesterol (OR 1.16, 95% CI 1.02 to 1.32, p=0.03) and type 2 diabetes (OR 1.09, 95% CI 1.01 to 1.17, p=0.02) were also causally associated with PDAC risk. BMI showed both direct and fasting insulin-mediated causal effects. - Conclusion We found strong evidence that BMI is causally associated with PDAC risk, providing support that obesity management may be a potential prevention strategy for reducing pancreatic cancer risk while fasting insulin and type 2 diabetes showed a suggestive association that should be further investigated.